2023
DOI: 10.1002/ejoc.202300137
|View full text |Cite
|
Sign up to set email alerts
|

Regiodivergent Synthesis of 11H‐Indolo[3,2‐c]quinolines and Neocryptolepine from a Common Starting Material

Abstract: A large number of diversely functionalized analogs of the bioactive natural products neocryptolepine and isocryptolepine have been prepared from a series of 3-bromoquinoline derivatives. The neocryptolepines were obtained by a Pd 0catalyzed CÀ C bond coupling followed by CÀ N bond formation in yields up to 80 %, whereas the indoloquinolines were prepared by a Suzuki-Miyaura cross-coupling followed by azidation-photochemical cyclization in yields ranging from traces to 95 % yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These studies showed that in addition to substrate 31 , substituted indoloquinolines were R 1 was either trifluoromethoxy (95 % yield), methyl (91 % yield), or fluorine (84 % yield) with the remaining R‐groups being hydrogen was formed in good yields (Scheme 13). [30] Other functional groups in this position gave relatively poor yields. For example, when R 1 was a methoxy group the indoloquinoline was only formed in 49 % yield.…”
Section: Our Approaches Towards Isocryptolepine and Analogues Thereofmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies showed that in addition to substrate 31 , substituted indoloquinolines were R 1 was either trifluoromethoxy (95 % yield), methyl (91 % yield), or fluorine (84 % yield) with the remaining R‐groups being hydrogen was formed in good yields (Scheme 13). [30] Other functional groups in this position gave relatively poor yields. For example, when R 1 was a methoxy group the indoloquinoline was only formed in 49 % yield.…”
Section: Our Approaches Towards Isocryptolepine and Analogues Thereofmentioning
confidence: 99%
“…Irradiating aryl azide 45 in α,α,α-trifluorotoluene with a 125 W medium-pressure mercury lamp at room temperature at primarily 254 nm gave a clean conversion to the desired product in 95 % yield after a simple work-up. [30] The conditions developed for the photolytic conversion of aryl azide 45 to indoloquinoline 31 was also used in order to prepare a range of analogues of compound 31. These studies Scheme 10.…”
Section: Photochemical Synthesis Of Isocryptolepine Precursor 31mentioning
confidence: 99%
See 2 more Smart Citations